Mechanical performances and stress states of rock bolts under varying loading conditions. (February 2016) - Kang, H.; Wu, Y.; Gao, F.; Jiang, P.; Cheng, P.; Meng, X.; Li, Z.
Highlights: The average cross section shrinkage of the threads was about 30% less than that of the rebar. Installation angle of rock bolt is a key factor to bolt end failure. Thread suffers distinct stress concentrations in the valleys of the thread teeth. Abstract: A comprehensive study including laboratory tests and numerical modeling was performed to investigate factors of rock bolt fracture. Experimental tests were performed to evaluate the mechanical performances of bolt ends including the thread and adjacent. The effects of installation angle, pretension and accessories (plate, washer and nut) were evaluated. It is found that a bolt installed with an oblique angle to roadway surface suffers a complex stress combination of tensioning, bending and twisting on the bolt. This complex stress is much greater than the tensile stress, leading to cracking and growth at the location of bending causing the thread to fail even though the tensile stress is less than the yield strength. Bolt thread is more vulnerable to fracture than rebar.